James Wadsworth family papers - Wadsworth, James, 1768-1844.; Hay, John, 1838-1905.; Lincoln, Abraham, 1809-1865.; Wadsworth, James S. (James Samuel), 1807-1864.; Wadsworth, James Wolcott, 1846-1926.; Wadsworth, James Wolcott, 1877-1952.; Wadsworth, William, 1761-1833.
Correspondence, diaries, financial papers, scrapbooks, clippings, photographs, and other papers of the family of James Wadsworth (1768-1844) and his brother, William Wadsworth (1761-1833), who settled in Geneseo, N.Y., in 1790 and endowed schools and libraries there.
Includes papers of James S. Wadsworth (1807-1864), son of James Wadsworth, Union Army officer who fought in the battle of Gettysburg, Pa., and was mortally wounded in the battle of the Wilderness (Va.); James Wolcott Wadsworth (1846-1926), son of James S. Wadsworth, Union Army officer, state legislator, and U.S. representative from New York; and James Wolcott Wadsworth, Jr. (1877-1952), U.S. senator and representative from New York and chairman, National Security Training Commission, whose congressional papers comprise the bulk of the collection. Also includes papers of James Wolcott Wadsworth, Jr.'s father-in-law, John Hay (1838-1905), diplomat and U.S. secretary of state (1898-1905), whose letters comment on life in London, England, and Washington, D.C.
Also included are a letter (1864 July 9) from Abraham Lincoln to Horace Greeley promising safe conduct for any emissaries of peace, abandonment of slavery, or restoration of the Union from Jefferson Davis; an album of autographed photographs of leaders in the Lincoln administration; and letters of Theodore Roosevelt.
Photograph album also available through the Library of Congress Web site, Words and Deeds in American History.
Landowner, reformer, and philanthropist whose family settled Geneseo, N.Y.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Davis, Jefferson, -- 1808-1889.; Greeley, Horace, -- 1811-1872 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Wadsworth family; United States. -- Army -- Officers; United States. -- Congress; United States. -- Department of State; United States. -- National Security Training Commission; Diplomatic and consular service, American -- Great Britain; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Libraries -- New York (State) -- Geneseo -- Endowments; Schools -- New York (State) -- Geneseo -- Endowments; Slavery -- Southern States; Wilderness, Battle of the, Va., 1864.; Geneseo (N.Y.) -- History; London (England) -- Social life and customs -- 19th century; New York (State) -- Politics and government -- 1865-1950.; Pennsylvania -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Autographs; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Casualties; United States -- History -- Civil War, 1861-1865 -- Peace; United States -- Politics and government -- 1865-1933.; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Washington (D.C.) -- Social life and customs -- 19th century; Landowners; Philanthropists; Reformers